Related Results to Hybrid Pair of Mappings and Applications in Bipolar Metric Spaces - G. N. V. Kishore; K. P. R. Rao; A. Sombabu; R. V. N. S. Rao (Journal of Mathematics)
In this paper, we introduce the concept of multivalued contraction mappings in partially ordered bipolar metric spaces and establish the existence of unique coupled fixed point results for multivalued contractive mapping by using mixed monotone property in partially ordered bipolar metric spaces. Some interesting consequences of our results are obtained.